PENERAPAN TERAPI BEHAVIOR TERHADAP SIKAP HIPERAKTIF PADA ANAK ADHD - Gustia Sepriani Putri (Universitas Karimun Prodi S1 Pendidikan Luar Biasa, 2023)
ADHD is an acronym for Attention Deficit Hyperactivity Disorder. It is usually used to describe children who have three main types of problems, namely: overactive behavior (hyperactivity), impulsive behavior, and difficulty paying attention/concentration. Because they are overly active and impulsive, children with ADHD often find it difficult to fit into school. Often they also have problems getting along with other children. These difficulties can continue as they grow older, if they do not get the help they need. One way to reduce children's hyperactivity is behavior therapy, which is a technique used to complete behavior caused by encouragement and encouragement to meet life's needs, which is carried out through a learning process so that they can act and behave more effectively. then able to respond to situations and problems in an effective and efficient manner. This activity is called learning. The method in this study used literature review studies, from several previous journals that had been reviewed by the authors, to get the result that this behavior therapy can reduce hyperactivity in children with ADHD.